Modulating physicochemical, antimicrobial and release properties of chitosan/zein bilayer films with curcumin/nisin-loaded pectin nanoparticles. (December 2022) - Zhang, Liming; Chen, Danying; Yu, Dawei; Regenstein, Joe M.; Jiang, Qixing; Dong, Junli; Chen, Wanwen; Xia, Wenshui
Abstract: This study aimed to develop a chitosan/zein based bilayer film loaded with nanoparticles (0, 1, 2, and 3%) as a reinforcing and functional agent and to investigate the effects of NPs on the physicochemical properties and structural attributes of the film. Curcumin-loaded pectin-based nanoparticles (NPs) with antimicrobial nisin were prepared using a combination of anti-solvent precipitation and complexation, and embedding NPs into the chitosan matrix to improve the physicochemical and functional properties of the chitosan/zein bilayer films. The average particle size and ζ-potential of the NPs were 143 nm and −33.0 mV, respectively. The scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis showed that the NPs had good compatibility with the film matrix and filled void spaces in the film matrix, which significantly improved the mechanical properties of the bilayer films (elongation at break increased from 63.2 to 86.8%; tensile strength increased from 32.4 to 45.1 MPa). The NPs bilayer films had higher barrier properties and thermal stability as well as UV blocking properties compared to bilayer films without NPs, while the controlled release of the active agents was sustainable. Likewise, the antimicrobial activity against the food-borne pathogens Staphylococcus aureus and Escherichia coli and the antioxidant activity of the NPs bilayer films depended on the NPs loading. The results suggested new design principles for chitosan/zein bilayer biofilms for potential use with sustainable food packaging, where the properties of the bilayer films could be tailored by controlling the concentration of NPs. Graphical abstract: Image 1 Highlights: Curcumin-loaded pectin nanoparticles mediated by nisin were fabricated. Bilayer active film with nanoparticles was prepared using Layer-by-Layer casting. Nanoparticles addition to the bilayer active film improved its physical properties. Controlled release effect was achieved by incorporating nanoparticles.